Applying research findings in comprehension to classroom practice - Wolfe, Josephine B. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1967)
An address for classroom teachers is presented which considers the nature of comprehension and the processes involved in teaching children to comprehend what they read. A review of the research on comprehension since 1960 is given. The following topics are discussed--the process of comprehending, the kinds of comprehension, the relationship between comprehension and concept development, and the place of word perception in comprehension. Some applications of what is known about comprehension to classroom procedures are suggested. This paper was presented at the international reading association conference (Seattle, may 4-6, 1967). (rh)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cognitive Processes; Comprehension; Concept Formation; Concept Teaching; Creative Reading; Critical Reading; Problem Solving; Reading Comprehension; Reading Development; Reading Research; Reading Skills; Word Recognition; University of Scranton PA